In silico Determination of Host-Viral Interaction of Apoptotic Mimicry Pathway Proteins During Hepatitis B Viral Pathogenesis - Prachie Sharma; Kamal Rawal; kapila Kumar (Universitas Gadjah Mada, 2023)
Viruses are the opportunistic pathogens that have developed several elegant strategies to deploy their host systems for a pathogenic invasion. Viral apoptotic mimicry is characterized by the exposure of host cell phospholipid, the phosphatidylserine which marks the host cell for apoptotic activation. The Hepatitis b virus, an enveloped virus has recently been found to interact with Phosphatidylserine (Ptdser) on the host through its large surface protein experimentally. Nonetheless, the employment of apoptotic mimicry during the pathogenesis of HBV has not been determined. Therefore, in the present study, we attempt the in-silico exploration of the interaction of the apoptosis initiating receptors activated by Phosphatidylserine Receptors such as TIM3, AXL, MERTK and GAS6 by Hepatitis B Virus L protein. Molecular Docking of Phosphatidylserine Receptor were studied to observe protein – protein interaction against Surface L Protein of Hepatitis B Virus by using online protein interaction software. It was found from the in-silico studies that Phosphatidylserine Receptors i.e. TIM3 (PDB: 5F71), AXL (PDB: 5U6B), MERTK (PDB: 2POC) and Gas6 (Growth Arrest Specific protein 6) (PDB: 2C5D) have shown effective binding efficacy against Surface L Protein of Hepatitis B Virus, whereas TIM3 (PDB: F71) and Gas6 (PDB: 2C5D) has shown maximum binding energy with respect to both the software used to analyse the protein-protein docking. This interaction study can form the basis of the experimental attempt in understanding the viral-host protein interaction pattern during hepatitis b viral infection.